Improvement of performance of ultra-high performance concrete based composite material added with nano materials (Fracture and Structural Integrity, 2016)
Ultra-high performance concrete (UHPC), a kind of composite material characterized by ultra high strength, high toughness and high durability. It has a wide application prospect in engineering practice. But there are some defects in concrete. How to improve strength and toughness of UHPC remains to be the target of researchers. To obtain UHPC with better performance, this study introduced nano-SiO2 and nano-CaCO3 into UHPC. Moreover, hydration heat analysis, X-Ray Diffraction (XRD), mercury intrusion porosimetry (MIP) and nanoindentation tests were used to explore hydration process and microstructure. Double-doped nanomaterials can further enhance various mechanical performances of materials. Nano-SiO2 can promote early progress of cement hydration due to its high reaction activity and C-S-H gel generates when it reacts with cement hydration product Ca(OH)2. Nano-CaCO3 mainly plays the role of crystal nucleus effect and filling effect. Under the combined action of the two, the composite structure is denser, which provides a way to improve the performance of UHPC in practical engineering.
Keywords: Composite material; Nano material